Compilation of empirical knowledge of weed potatoes (Solanum L.) from the Potosino-Zacatecano Altiplano - Luna Cavazos, Mario; García Moya, Edmundo (Instituto de Ecología, A.C., 1989)
Management practices and economic importance of Solanum cardiophyllum Lindl. And S. ehrenbergii (Bitt.) Rydb., growing as weeds in agricultural fields were studied. The species are receive many local names; “papa el monte” being the most common. The tubers of both species are utilized mainly for self consumption, but some are also sold in local markets principally from February through May. The recollection is carried out from November to April, when fields are plowed, and the tubers are brought up to the surface; people also search for them guided by dead aerial portions using hand tools. The use of farm machinery for agricultural practices destroys the plants and tubers, diminishing the populations. Traditional farmers promote the growth and development of the potato plants favoring their conservation as a potential resource.